Innate Immunity in Lobsters: Partial Purification and Characterization of a Panulirus cygnus Anti-A Lectin. (5th March 2012) - Flower, Robert L. P.
Abstract : A lectin detected in haemolymph from the Australian spiny lobster Panulirus cygnus agglutinated human ABO Group A cells to a higher titre than Group O or B. The lectin also agglutinated rat and sheep erythrocytes, with reactivity with rat erythrocytes strongly enhanced by treatment with the proteolytic enzyme papain, an observation consistent with reactivity via a glycolipid. The lectin, purified by affinity chromatography on fixed rat-erythrocyte stroma, was inhibited equally by N -acetylglucosamine and N -acetylgalactosamine. Comparison of data from gel filtration of haemolymph (behaving as a 1, 800, 000 Da macromolecule), and polyacrylamide gel electrophoresis of purified lectin (a single 67, 000 Da band), suggested that in haemolymph the lecin was a multimer. The purified anti-A lectin autoprecipitated unless the storage solution contained chaotropic inhibitors (125 mmol/L sucrose: 500 mmol/L urea). The properties of this anti-A lectin and other similar lectins are consistent with a role in innate immunity in these invertebrates.